Use of Gestational Surrogates for Women With Eisenmenger Syndrome: A Cost-Effectiveness Analysis. Issue 7 (July 2021) - Clennon, Emily K.; Pare, Emmanuelle; Amato, Paula; Caughey, Aaron B.
Abstract : (Abstracted from J Matern Fetal Neonatal Med 2021;34:526–531) One clear contraindication to pregnancy is Eisenmenger syndrome (ES), a rare complication affecting pulmonary function. Up to 50% of ES cases result in maternal deaths.